Design and Simulation Investigations of W-Band Second Harmonic Periodically Dielectric-Loaded Gyro-TWT - Akash A.; Thottappan M. (My University, 2025)
In this article, the complete design and beam-wave interaction studies of W-band gyro-TWT amplifier have been presented. The gyro-TWT has been designed to operate at second harmonic TE 02 mode to reduce the magnetic field requirement. A triode-type magnetron injection gun has been designed and optimized for low-velocity spread using E-GUN. A novel, mode selective input coupler with a gradually tapered slotted waveguide has been used to feed the desired TE 02 mode and suppress the reflection and spurious oscillations at the input end (upstream). To abridge the absolute instability of the operating mode and backward wave oscillations caused by spurious modes, a periodic lossy dielectric-loaded RF structure has been adopted. The particle-in-cell simulation of the amplifier predicted a peak RF output power of ∼500 kW with ∼3.6 GHz bandwidth, ∼20% efficiency, and ∼32.2 dB saturated gain for the DC input of 100 kV, ∼25 A with 4% axial velocity spread and velocity ratio of 1.22. Further, to extract the output power with minimum reflection, a double-disc window has been studied. An undepressed curved collector is also designed using E-GUN and its simulation predicted a maximum heat wall loading of ∼0.39 kW /cm2. © 2022 IETE.